HER-2 Expression in Immunohistochemistry Has No Prognostic Significance in Gastric Cancer Patients - Agnieszka Halon; Piotr Donizy; Przemyslaw Biecek; Julia Rudno-Rudzinska; Wojciech Kielan; Rafal Matkowski (The Scientific World Journal)
The role of HER-2 expression as a prognostic factor in gastric cancer (GC) is still controversial. The aim of the study was to asses HER-2 status, its correlations with clinicopathological parameters, and prognostic impact in GC patients. Tumor samples were collected from 78 patients who had undergone curative surgery. In order to evaluate the intensity of immunohistochemical (IHC) reactions two scales were applied: the immunoreactive score according to Remmele modified by the authors and standardised Hercep test score modified for GC by Hofmann et al. The HER-2 overexpression was detected by IHC in 23 (29.5%) tumors in Hercep test (score 2+/3+) and in 24 (30.7%) in IRS scale (IRS 4–12). The overexpression of HER-2 was associated with poorly differentiated tumors, but this correlation was not significant (P=0.064). No relationship was found between HER-2 expression and primary tumor size and degree of spread to regional lymph nodes. Both univariate and multivariate analyses revealed that TNM stage and patient’s age were the crucial negative prognostic factors. No correlation was observed between patient survival and expression of HER-2 estimated using both scales. This research did not confirm HER-2 expression (evaluated with immunohistochemistry) value as a prognostic tool in GC.